Enhancing soil fertility and maize yield using liming amendments - Meppe, F.; Osiname, O.; Bilong, P. (African Journals Online, 2007)
The low fertility level of some soils of the Western Highlands of Cameroon prompted a study of the response of maize (Zea mays L.) and some major soil chemical properties to liming. The first manufactured local lime “Agri 56” was tested along with 3 imported types (calcitic, slaked, and dolomitic), each one at four rates (2, 5, 10 and 15 tons ha-1), replicated three times in a randomized complete block design. Data were collected for 4 years. Maize yields were increased with increased lime rates, but not significantly after 2 tons ha-1. There was no interaction between liming rate and source. Liming source had no significant effect on maize yields; however, Agri 56 generated the highest yield. Soil pH was increased with increase in liming rates though not significantly, and exchangeable Al was neutralized completely after 2 tons ha-1. Soil calcium and magnesium contents significantly (p>0.05) increased with increments in lime rates. The significance to maize cropping is discussed.